RANCANG BANGUN APLIKASI WEBSITE SEBAGAI MEDIA MANAJEMEN PENDAFTARAN PEMESANAN GEDUNG AULA METRO BAUBAU - Liwang, Rasyid; Hendrawan, Nalis; Riswandi, Riswandi (Prodi Teknik Informatika Unidayan Baubau, 2019)
Baubau Metro Hall is one of the multi-purpose buildings in the Baubau City area. The location of the Baubau Metro Hall is very strategic, namely in the District of Betoambari, precisely in front of the Betoambari Stadium. Registration for the Baubau Metro hall building reservation is still conventional in that the community must come to the place to order a building and it is not uncommon for the community to cancel orders because the predetermined schedule has been ordered by someone else. This study aims to design and create a website application as a media for registration management for the Baubau Metro Hall Building. The data collection method used was observation and interview with the management of the Baubau Metro Hall Building. The website is created using HyperText Processor (PHP) as its programming language and Mysql as its database. The results of this study are that with the application made it can make it easier for people to register and find out the schedule for using the Baubau Metro Hall.Keywords: Building Hall, Metro, Registration, Website.Keywords: Building Hall, Metro, Registration, Website.